POLA ASUH ORANG TUA DALAM MENGEMBANGKAN POTENSI ANAK CIBI (CERDAS ISTIMEWA DAN BERBAKAT ISTIMEWA) DI SD MUHAMMADIYAH DHARMA TANJUNG KECAMATAN CAMPLONG KABUPATEN SAMPANG - Massunah, Massunah; Zakariya, Din Muhammad (Jurnal Staika: Jurnal Penelitian dan Pendidikan, 2025)
This study aims to examine how parents' parenting styles contribute to the development of their children's potential, how the potential of CIBI children manifests, and whether there are supporting and inhibiting factors in developing the potential of CIBI children at Muhammadiyah Dharma Tanjung Elementary School in grades IV, V, and VI. This research employs a descriptive-qualitative method using interviews, observation, and documentation as data collection techniques. The data analysis process includes data categorization, data presentation, and drawing conclusions. Data validity is ensured through participant extension, careful observation, triangulation, and verification. The results of this study conclude that, first, the parenting styles applied by parents include democratic, neglectful, authoritarian, and permissive styles. Second, the children's potential includes intellectual potential, physical potential, and musical or artistic intelligence. Third, the economic background (whether high or low) of the parents significantly influences the development of CIBI children's potential, based on field observations and findings, acting as either a support or barrier to the development of the child's potential.